2017
DOI: 10.26737/jetl.v2i1.152
|View full text |Cite
|
Sign up to set email alerts
|

Efforts to Increase Students Reading Interest on Educational Reference Through Classical Guidance and Counseling Experiential Learning Model

Abstract: The objective of the research is improving students’ reading interest on educational references through classical guidance and counseling experiential learning model. The research was carried out at STKIP Pacitan on the second semester in 2016/2017 academic year. The subject of the research was 20 fourth semester students of STKIP Pacitan. The method of the research was Classroom Action Research (CAR). The data was collected through 3 (three) stages namely: data reduction, data presentation, and data conclusio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 1 publication
0
4
0
3
Order By: Relevance
“…Those activities are referring to one English skill integrated into other skills. Based on previous research, the use of classical guidance and counseling experiential learning model gave opportunity for students to deliver their ideas related with the problems in reading interest, and then, being solved together through critical thinking (Sutarti, 2017). The other research ("The Efforts to Foster Students' Skill in Making Questions through Thinking Tool (Question Matrix) Development," 2019) found that Question Matrix had helped the students in making questions.…”
Section: The Dominant English Skill Practiced By the Studentsmentioning
confidence: 99%
“…Those activities are referring to one English skill integrated into other skills. Based on previous research, the use of classical guidance and counseling experiential learning model gave opportunity for students to deliver their ideas related with the problems in reading interest, and then, being solved together through critical thinking (Sutarti, 2017). The other research ("The Efforts to Foster Students' Skill in Making Questions through Thinking Tool (Question Matrix) Development," 2019) found that Question Matrix had helped the students in making questions.…”
Section: The Dominant English Skill Practiced By the Studentsmentioning
confidence: 99%
“…Because the current study uses qualitative research methods, the research will produce and manage descriptive data, such as interview transcripts, field notes, pictures, photos, video recordings and so on (Setyosari, 2013). This research is said to be qualitative because basically this research aims to examine or examine an object in a natural setting without any manipulation in it, and the expected results are not based on quantitative measures, but the meaning or aspect of the observed phenomenon.…”
Section: Methodsmentioning
confidence: 99%
“…The research paper used Classroom Action Research (CAR) as a technique of getting detailed information from the respondents' participation in the research paper. The researchers and or the educational practitioners (Sutarti (2017) investigate the respondents in their natural settings to improve their teaching practices. The purpose of the CAR is to advance rationale and quality including (a) socioeducational training, (b) knowledge of the practice, (c) the milieu at which practice is done.…”
Section: Methodsmentioning
confidence: 99%